Green innovation on determinants of organizational performance with management commitment as a moderating variable - Fisla Wirda; Tuti Azra; Jumyetti Jumyetti; Herizon Herizon; Ariani Tanjung (Intangible Capital)
Purpose: The objective of this study is to analyze the effect of Green Innovation to business performance, the effect of management commitment to green innovation, effect of management commitment to organizational performance, and effect of green innovation to  performance with management commitment as a moderating variable. Design/methodology/approach: This research used a quantitative approach, using questionnaires as the primary data source. The study population consisted of the culinary sector in the city of Padang. The sample size was 100 managers from the culinary sector, selected using a purposive sampling technique. The data analysis technique applied was Structural Equation Modeling (SEM), with AMOS software used for data processing. Findings: There are 24 indicators whose values are valid because their standardized estimated value is ≥ 0.5, while 8 indicators are invalid. Goodness of Fit Test show that the model is an overall fit, all indicators meet the cut-off values. The result of The hypotheses show that  green innovation significantly affects business performance, management commitment significantly affects green innovation, management commitment significantly affects business performance. However, management commitment does not moderate the relationship between green innovation and business performance. Research limitations/implications: Many factors influence green innovation that has not been discussed in this research, such as knowledge and government roles. Future research should use this  variable as an antecedent variable to the green innovation. Practical implications: The findings of this research will contribute to development efforts, serving as an evaluation tool for the Padang City Government, particularly the Department of Environmental Affairs, about Regulation No. 36 of 2018 about green innovation movement among SMEs. Originality/value: most research on Green Innovation has been conducted in large companies, with very few studies focusing on small businesses. This research fills the gap in the literature on Green Innovation in Small and Medium Enterprises (SMEs).